2014
DOI: 10.1016/j.bbamem.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Strong dimerization of wild-type ErbB2/Neu transmembrane domain and the oncogenic Val664Glu mutant in mammalian plasma membranes

Abstract: Here, we study the homodimerization of the transmembrane domain of Neu, as well as an oncogenic mutant (V664E), in vesicles derived from the plasma membrane of mammalian cells. For the characterization, we use a Förster resonance energy transfer (FRET)-based method termed Quantitative Imaging-FRET (QI-FRET), which yields the donor and acceptor concentrations in addition to the FRET efficiencies in individual plasma membrane-derived vesicles. Our results demonstrate that both the wild-type and the mutant are 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…They were imaged using a Nikon Eclipse C1 laser scanning confocal microscope. Each vesicle was imaged using three separate scans: a donor scan, a FRET scan, and an acceptor scan, as described in previous publications (25,(33)(34)(35)(36). Following image acquisition, vesicles were processed using an in-house MATLAB script (21).…”
Section: Resultsmentioning
confidence: 99%
“…They were imaged using a Nikon Eclipse C1 laser scanning confocal microscope. Each vesicle was imaged using three separate scans: a donor scan, a FRET scan, and an acceptor scan, as described in previous publications (25,(33)(34)(35)(36). Following image acquisition, vesicles were processed using an in-house MATLAB script (21).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that a somatic mutation destabilizes dimer formation [49], while in another case, a disease-causing mutation was demonstrated to stabilize the dimer [50]. Missense mutations associated with cancer [51], Snyder-Robinson syndrome [19], and congenital heart diseases [52] were linked with altered protein-protein and protein-DNA interactions. In general, any deviation in affinity caused by mutation(s), enhanced or reduced, possesses a high risk of developing a disease.…”
Section: Impact Of Mutations On Protein-protein Protein-ligand and Pmentioning
confidence: 99%
“…If the proteins exist in a monomer-dimer equilibrium, the broad range of concentrations is required such that the association model can be fitted to the data. In the case of constitutively dimeric receptors, data over a broad range is required so we can convince ourselves that the receptors are indeed 100% dimeric, by the lack of dependence of FRET on concentration 7 . In this case, the measured FRET depends only on the Intrinsic FRET and the acceptor fraction.…”
Section: Technical Advantages Of the Qi-fret Methods In Rtk Researchmentioning
confidence: 99%
“…In this case, the measured FRET depends only on the Intrinsic FRET and the acceptor fraction. Since the acceptor fraction is known, the Intrinsic FRET can be directly determined for constitutive dimers 7 . In this case, the QI-FRET method can be used as a structural assay.…”
Section: Technical Advantages Of the Qi-fret Methods In Rtk Researchmentioning
confidence: 99%
See 1 more Smart Citation